A Study on Organizational Culture and Organizational Performance (International Journal of Innovative Research in Engineering & Management, 2021)
This review paper focuses on the definition and measurement  of organizational culture and sheds the light on the important  studies on the topic. It also sheds the light on the culture performance literature. This review paper also sheds the light  on the definition, conceptualization, and measurement of  organizational performance. This review paper has also showed  a number of studies that linked the relationship between  organizational culture and the organizational performance. Although there is no consensus on the definition of  organizational culture, most authors agreed that  organizational/corporate culture referred to something that is  holistic, historically determined (by founders or leaders),  related to things anthropologists study (like rituals and  symbols), socially constructed (created and preserved by the  group of people who together form the organization),soft, and  difficult to change.
Keywords: Financial Performance; Organizational Culture; Organizational Performance; Performance orientation